Influence of Precast Member Corbels on Seismic Performance of Precast Beam-Slab-Column Joints - Hongtao Liu; Pengchao Kong; Taoping Ye (Advances in Civil Engineering, 2021)
To improve the construction efficiency of precast structures, reinforced concrete corbels acted as support members are the most common connection method. This work presents the performance of a specific beam-to-column connection using corbels with different anchorage arrangements in precast beam-slab-column interior joint taken out from precast underground subway station. This paper investigates the performance of a specific full-scale precast concrete beam-slab-column interior joint with corbels and various connected methods subjected to low-cycle repeated loading. Meanwhile, the influences of concrete corbels (including column- and beam-end corbels) on the shear strength and deformation are investigated. The analyses results indicated that (1) corbels of the laminated beam (composite beam) can obviously improve the shear stress of the core region, which was beneficial for specimen design followed the strong-joint-weak-member concept; (2) a simplified approach to deal with the uneven thickness of corbels in the core region was proposed, which was utilized to study the effect of thickness on the shear performance of the core region; (3) the shear stress increased with respect to the compression stress, and the shear strain had a trend of decreasing according to calculating results using modified compression field theory; and (4) the deterministic expressions were proposed to predict the designed load of column corbels based on three different connection methods between laminated beams and core region of joint.